Republic or empire? The Philippine question - Bryan, William Jennings (Independence Co., 1899)
The Spanish-American war has involved the people of the United States in the discussion of a question entirely new to the present generation, a question of such vast importance that its final settlement will form an epoch in the history of the nation. The treaty of peace, now concluded, provides for the relinquishment by Spain of sovereignty over Cuba and also for the cession of Porto Rico and the Philippine Islands to the United States.